A large duplicated area in the polycystic kidney disease 1 (PKD1) region of chromosome 16 is prone to rearrangement. - Harris, P; Thomas, S; MacCarthy, AB; Stallings, R; Breuning, M; Jenne, D; Fink, T; Buckle, V; Ratcliffe, P; Ward, C (1994)
An area of 500 kb at the proximal end of the polycystic kidney disease 1 (PKD1) region has been mapped in detail, with 260 kb cloned in cosmids. The area cloned from normal individuals contains two homologous but divergent regions each of 75 kb, including the previously described marker 26-6. Pulsed-field gel electrophoresis identified a duplication of 75 kb of this region, referred to as the OX duplication (OXdup), in three patients with PKD1. The OXdup probably arose by an unequal exchange promoted by misalignment of partially homologous areas. Study of the OXdup in a large PKD1 family showed that it segregated with PKD1 in just one-half of the family, indicating that a recent crossover had occurred between the OXdup and PKD1 and showing that it was not a PKD1 mutation. Further analysis identified an OXdup breakpoint fragment: the OXdup was subsequently identified in 2 normal individuals of 110 assayed. The finding of the OXdup and in other individuals an 11-kb deletion (OXdel) at a similar point within this duplicated area indicates that this is an unusually unstable genomic region.